FORCED MIGRATION, SCHOOL WASTAGE AND REFUGEE GOVERNANCE: AN EMPIRICAL ANALYSIS OF THE SITUATION OF REFUGEE CHILDREN IN CAMEROON - Jeanne EPOTO IBON NDOME; Jean-Pierre MBAME (Universitaria Publishing House, Craiova, 2023)
Education is an essential element in the development of a nation, as it is indispensable for the formation of men. It is in this sense that the general objective of this work was to identify the incidence of forced migration and refugee governance that could be at the origin of school wastage among refugee children enrolled in Cameroon in refugee camps and their surroundings. From the results obtained, we found that school wastage in refugee camps in Cameroon is due to a multitude of elements, mainly the living conditions in the camps, 30% of the subjects interviewed pointed to this as the main cause. 5% emphasized the infrastructure and schooling conditions (overcrowding, lack of school supplies, lack of facilities, etc.). Let us also note the existence of certain beliefs that are at the origin of gender-based discrimination; 30% of the parents interviewed believe that girls should not go to school and should stay at home to perform domestic tasks and prepare for marriage; 50% of the parents interviewed believe that it is not useful to send their children to school; 20% of the parents interviewed acknowledge that they have sent their children to school on the initiative of the NGOs. Our work has allowed us to describe and identify possible factors associated with the problem of migration and refugee governance in schools located in and around refugee camps.